UGLYPH - 3D IMAGE PREPARATION AND DISPLAY SYSTEM - Meireles Acruche, Roberto; de Oliveria Matias, Ítalo; Giuseppe Pereira da Silva, Angelus; Muniz Barbosa, Thiago (LINKSCIENCEPLACE, 2026)
The anaglyph technique is known long ago, but is still the most simple and inexpensive for 3D viewing. This technique is mainly used for entertainment, but its use in education can greatly assist the content teaching which requires depth perception. There are many contents as well in geology, civil engineering, biology, medical and others. The anaglyph visualization is possible with two-color lenses glasses which is cheap and easy to make. The anaglyph preparation can be done with resources of image editors programs, but this is a laborious task. There are programs directed to this. The UGlyph is a program capable of connecting up even to two webcams to capture photos and videos and prepare with them anaglyph and anaglyph video that can be displayed in monitor on real-time. This paper presents the software that is freely available on network for download.